Peran Metode Bernyanyi Dalam Mengembangkan Kemampuan Kognitif Anak Usia Dini Di Tk Aisyiyah Al Amin Surakarta - Saky, Daiva Dahayu Kharisma; Widjanarko, Paulus; Wahyuseptiana, Yetty Isna (Lembaga Teewan Journal Solutions, 2026)
Singing as a teaching method in early childhood education plays a crucial role in stimulating children’s cognitive development through enjoyable, concrete, and repetitive learning activities. This study aims to describe the role of singing as a teaching method in developing the cognitive abilities of young children at Aisyiyah Al Amin Kindergarten in Surakarta. This study employs a descriptive qualitative approach. The research subjects consisted of one classroom teacher and 12 children aged 4–5 years in Group A, selected through purposive sampling. Data were collected through observation, semi-structured interviews, and document analysis. Data analysis utilized the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the singing method plays a role in developing three cognitive aspects based on the STPPA indicators, namely symbolic thinking, logical thinking, and learning and problem-solving. After ten learning sessions, no child was categorized as “Not Yet Developed.” Songs containing numbers, letters, colors, shapes, and simple cause-and-effect concepts help children remember, group, sequence, and understand learning material more effectively. Thus, the singing method can be used as an effective pedagogical strategy to support the cognitive development of young children.